Our experience with modified Sugiura’s procedure for the treatment of esophageal varices. - Estefan, Alberto; Carriquiry, Guillermo; Beguiristaín, Alberto; Pérez Billi, Luis; Lago, Fernando; Pignata, Daniel (Cirugía del Uruguay, 1984)
Sugiura's procedure basically includes: ample paraesophageai gastric devascularization, mucous transec• tion of the esophagus, selective vagotomy accompa• nied with pyloroplasty and splenectomy.